Creating 2D games with Unity : build a complete 2D game from start to finish using the Unity game engine - Manning, Jon (O'Reilly, 2016)
"You've downloaded the Unity software, you know what the Inspector is, and now you're ready to build something. In this course, you'll create an entire physics-based 2D game starring a gnome who is lowered down a well on a rope and goes searching for treasure. You'll start from an empty scene and finish with a complete polished game. Along the way you'll learn about game design, GUI setup, camera control, the game manager, gameplay practices, advanced graphics techniques, and the iterative nature of game development. Learn how to create 2D games using Unity game development software; discover how ragdolls work and how to create physics-based gameplay; learn how to manage gameplay with game managers and advanced game scripting; practice techniques for better camera control and for creating polished graphics; discover how the various pieces you build in Unity fit together to form gameplay; understand how to architect your games for easier changes"--Resource description page.